Automotive film containing organic silicon elastomer particles and preparation method thereof

By adding silicone elastomer particles with polar groups on the surface grafted into the matrix material of the automotive film, the shortcomings of the existing film materials in terms of wear resistance, touch and gloss are solved, and efficient performance improvement is achieved and Environmentally friendly production.

CN119161811APending Publication Date: 2024-12-20KUSN ACHILLES ARTIFICIAL LEATHER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324631.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing automotive film materials such as TPO, TPU or PVC are difficult to meet the wear resistance, touch and surface gloss at the same time. Traditional materials are prone to wear after long-term use, affecting their aesthetics and service life.

Method used

Add silicone elastomer particles with polar groups on the surface grafted to the base material of the automotive film, and adjust the surface gloss effect of the film by controlling the particle size and amount of the particles, and add flame retardant, light stabilizer and Heat stabilizer to improve flame retardancy and stability.

Benefits of technology

It realizes the better wear resistance, comfortable touch and adjustable surface gloss of automotive films, improves the flame retardant performance of the film and the stability of the high-temperature ultraviolet environment, and the process is free of solvent pollution, high production efficiency and low cost. , environmentally friendly and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005055069600000071
    Figure BDA0005055069600000071
Patent Text Reader

Abstract

The invention belongs to the technical field of automotive films, and discloses an automotive film containing organosilicon elastomer particles and a preparation method. The automotive film containing the organosilicon elastomer particles comprises a surface protection layer, wherein a pressure-sensitive adhesive layer and a release layer are sequentially arranged on the lower surface of the surface protection layer; the surface protection layer is prepared from the following raw materials: a base material, organic silicon elastomer particles, a plasticizer, a heat stabilizer, a light stabilizer, an antioxidant, an ultraviolet light absorber, a flame retardant, hydrophobic modified montmorillonite and an ethylene-vinyl acetate copolymer. According to the application, the organic silicon elastomer particles with polar groups grafted on the surfaces are added into the vehicle TPO / TPU / PVC film base material, so that the vehicle film has better wear resistance and more comfortable touch feeling, and meanwhile, the surface gloss effect of the vehicle film is regulated and controlled by controlling the particle size and dosage of the organic silicon elastomer particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automotive films, and in particular to an automotive film containing silicone elastomer particles and a preparation method thereof. Background Art

[0002] Automotive film materials are important materials used in automobile manufacturing to improve vehicle performance, aesthetics and protection needs. They include automotive window films, automotive paint protection films, and other film materials used for automotive interior and exterior. With the rapid development of the automotive industry, the performance requirements for automotive film materials are increasing. Especially in terms of wear resistance, touch and surface gloss, the existing direct use of TPO, TPU or PVC films is often difficult to meet all of them at the same time. After long-term use, the surface of traditional film materials is prone to wear, affecting the appearance and service life. To solve this problem, the industry continues to explore new materials and technical solutions. Summary of the invention

[0003] The present invention aims to solve the technical problems that the base materials used in existing automotive films, such as TPO, TPU and PVC, have insufficient wear resistance, a less silky touch and difficult to control surface gloss. By adding specific silicone elastomer micron particles, the above-mentioned properties of the automotive film material are improved. The present application provides an automotive film containing silicone elastomer particles and a preparation method.

[0004] In a first aspect, the present application provides a film for automobiles containing silicone elastomer particles, comprising a surface protection layer, wherein a pressure-sensitive adhesive layer and a release layer are sequentially provided on the lower surface of the surface protection layer; The surface protection layer comprises the following raw materials in parts by weight: 60-85 parts of base material, 5-20 parts of silicone elastomer particles, 20-30 parts of plasticizer, 1-2 parts of heat stabilizer, 0.5-2 parts of light stabilizer, 0.5-1 parts of antioxidant, 0.5-1 parts of ultraviolet absorber, 1-2 parts of flame retardant, 3-5 parts of hydrophobically modified montmorillonite, and 8-15 parts of ethylene-vinyl acetate copolymer.

[0005] Optionally, the base material includes one or more of TPO, TPU and PVC.

[0006] By adopting the above technical scheme, TPO, TPU or PVC are selected as the matrix materials in this application, all of which are polymer materials. The three have no or little cross-linking in chemical structure, and their molecules are basically linear structures, which can be heated and plasticized, and have excellent mechanical properties. They can be adjusted by changing the ratio of the reaction components, and maintain good elasticity and wear resistance in the entire hardness range. In addition, no organic solvents are used in the formulation of the surface protective layer in this application, and there is no solvent pollution. The process operation is simple, the production efficiency is high, and the process is stable; the obtained product has excellent mechanical properties, good quality, a large range of hardness adjustment, and low cost. The production process and products are completely environmentally friendly, without any environmental pollution; the hardness adjustment range is wide, and the product has good hydrolysis resistance and feel.

[0007] Optionally, polar groups are grafted onto the surface of the organosilicon elastomer particles.

[0008] Optionally, the polar groups include two or more of acrylate groups, acrylonitrile groups, epoxy groups and amino groups.

[0009] Preferably, the surface of the silicone elastomer particles is grafted with acrylate groups and epoxy groups.

[0010] By adopting the above technical scheme, the organic silicon elastomer microparticles in the present application have the characteristics of high heat resistance, good dispersibility, low refractive index, high transparency, etc. The raw materials include polysiloxane containing unsaturated carbon-carbon bonds, catalysts and curing delay agents, etc. In the preparation process, the liquid polysiloxane is sheared into micron-sized liquid particles and dispersed in water after being wrapped by an emulsifier to form a polysiloxane water dispersion, which is then cured by microwave heating and cured into an organic silicon elastomer under the catalysis of a catalyst containing platinum group metals. The prepared organic silicon elastomer has the advantages of heat resistance, easy dispersion, low refractive index, etc. The preparation method of grafting polar groups on the surface of organic silicon elastomer microparticles in the present application is to add a polar modifier to a mixture of organic silicon elastomer microparticles and water, then initiate polymerization, and separate the polymerization product to obtain surface-modified organic silicon elastomer microparticles; wherein the polar modifier is a monomer or oligomer containing at least one polar group. In the present application, silicone elastomer particles with polar groups grafted on the surface are used to improve the surface polarity and tension compared to silicone elastomer particles without polar groups grafted, effectively solving the adhesion, agglomeration and precipitation problems of pure silicone elastomer particles in matrix materials such as TPO, TPU or PVC, and overcoming the problem of easy agglomeration and fluidity of pure silicone elastomer particles as a wear-resistant agent in the matrix material.

[0011] Preferably, the amount of the silicone elastomer particles is 8-15 parts by weight.

[0012] Optionally, the particle size of the silicone elastomer particles is 2-3 um.

[0013] Optionally, the particle size of the silicone elastomer particles is 6-8 um, or the particle size of the silicone elastomer particles is 12-15 um.

[0014] By adopting the above technical solution, silicone elastomer particles of different particle sizes can be selected according to needs, so as to adjust the surface gloss of the film; when pursuing a micro-matt effect on the surface, silicone elastomer particles with a particle size of 2-3 microns can be used; when pursuing a significant matt effect, silicone elastomer particles with a particle size of 6-8 microns or a particle size of 12-15 microns can be used.

[0015] Optionally, the hydrophobically modified montmorillonite is cross-linked and modified by using KH550 coupling agent.

[0016] Optionally, the flame retardant comprises a mixture of sodium hydroxymethyl lignin sulfonate and triphenyl phosphate in a weight ratio of 1-3:0.5-1.

[0017] By adopting the above technical scheme, sodium hydroxymethyl lignin sulfonate is used as a flame retardant. Sodium hydroxymethyl lignin sulfonate is a lignin derivative sodium lignin sulfonate modified by hydroxymethylation. The modification is beneficial to improve its reaction activity and promote the cross-linking of active groups such as hydroxyl groups in its structure with the base material. At the same time, sulfonate flame retardants can promote the release of carbon dioxide and water, the generation of phenolic substances and the generation of aromatic and aliphatic compounds, thereby increasing the carbonization rate of the base material during combustion. The cross-linked structure is also conducive to the formation of a dense carbon layer to prevent oxygen and heat from being transferred to the inside of the plastic to improve the flame retardant effect. Triphenyl phosphate is added to the base material as an organic phosphate and used in combination with hydrophobically modified montmorillonite, sodium hydroxymethyl lignin sulfonate, etc., which can significantly improve the flame retardant and smoke suppression properties of the obtained automotive film. Triphenyl phosphate can also be added to the base material as a plasticizer to make the base material easier to melt and form.

[0018] Optionally, the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 15-30 wt%.

[0019] In a second aspect, the present application provides a method for preparing the above-mentioned automotive film containing silicone elastomer particles, comprising the following steps: S1, drying the base material in a dryer to remove moisture, adding the dried base material and the remaining raw materials into a reaction vessel according to the formula amount for melt blending, controlling the temperature to 150-180° C., to obtain a premix; S2. Extruding the premix obtained in step S1 to form a uniform film, cooling it in cooling water, shaping it, and cutting it, coating a pressure-sensitive adhesive on one surface of the cut film to form a pressure-sensitive adhesive layer, and covering the pressure-sensitive adhesive layer with release paper to form a release layer, thereby obtaining a vehicle film containing silicone elastomer particles.

[0020] Optionally, in step S2, the extrusion process is carried out in a twin-screw extruder, and the temperature of zone 1 of the twin-screw extruder is 130-135°C, the temperature of zone 2 is 140-145°C, the temperature of zone 3 is 155-160°C, the temperature of zone 4 is 170-175°C, the temperature of zone 5 is 180-185°C, the temperature of zone 6 is 190-195°C, the temperature of zone 7 is 190-195°C, the temperature of zone 8 is 190-195°C, and the temperature of zone 9 is 180-185°C; the rotation speed of the twin-screw extruder is 100-120rpm; and the head temperature of the twin-screw extruder is 180-185°C.

[0021] In summary, the present invention includes at least one of the following beneficial technical effects: 1. In this application, organic silicon elastomer particles with polar groups grafted on the surface are added to the automotive TPO / TPU / PVC film matrix material, so that the automotive film has both good wear resistance and comfortable touch. At the same time, the surface gloss effect of the automotive film is regulated by controlling the particle size and amount of organic silicon elastomer particles. This application also adds flame retardants, light stabilizers, heat stabilizers and ultraviolet absorbers to the matrix material to enhance the flame retardancy of the automotive film and its stability in high temperature and ultraviolet environments.

[0022] 2. The surface protective layer of the automotive film in this application does not use any organic solvents, there is no solvent pollution, the process operation is simple, the production efficiency is high, and the process is stable; the resulting product has excellent mechanical properties, good quality, a wide range of hardness adjustment, and low cost. DETAILED DESCRIPTION

[0023] The present application designs a vehicle film containing silicone elastomer particles, including a surface protection layer, the lower surface of which is sequentially provided with a pressure-sensitive adhesive layer and a release layer; the surface protection layer comprises the following raw materials in parts by weight: 60-85 parts of a base material, 5-20 parts of silicone elastomer particles, 20-30 parts of a plasticizer, 1-2 parts of a heat stabilizer, 0.5-2 parts of a light stabilizer, 0.5-1 parts of an antioxidant, 0.5-1 parts of an ultraviolet absorber, 1-2 parts of a flame retardant, 3-5 parts of hydrophobically modified montmorillonite, and 8-15 parts of an ethylene-vinyl acetate copolymer.

[0024] The automotive film containing silicone elastomer particles of the present application is prepared by the following method, including the following steps: S1, drying the base material in a dryer to remove moisture, adding the dried base material and the remaining raw materials into a reaction vessel according to the formula amount for melt blending, controlling the temperature to 150-180° C., to obtain a premix; S2. Extruding the premix obtained in step S1 to form a uniform film, cooling it in cooling water, shaping it, and cutting it, coating a pressure-sensitive adhesive on one surface of the cut film to form a pressure-sensitive adhesive layer, and covering the pressure-sensitive adhesive layer with release paper to form a release layer, thereby obtaining a vehicle film containing silicone elastomer particles.

[0025] The technical problem solved by the present application is that the existing direct use of TPO, TPU or PVC films is often difficult to meet the requirements of wear resistance, touch and surface gloss at the same time. After long-term use, the surface of traditional film materials is prone to wear, which affects the appearance and service life. In the present application, silicone elastomer particles with polar groups grafted on the surface are added to the automotive TPO / TPU / PVC film matrix material to make the automotive film have both good wear resistance and more comfortable touch. At the same time, the surface gloss effect of the automotive film is regulated by controlling the particle size and dosage of the silicone elastomer particles.

[0026] The present application is further described in detail below in conjunction with specific embodiments.

[0027] Examples 1-5 Examples 1-5 are automotive films made with different raw material ratios. The difference is that the raw material ratios of the surface protective layer of the automotive film are different, as follows: The surface protection layer of the automotive film in Example 1 includes the following raw materials in parts by weight: 5 parts of silicone elastomer particles, 70 parts of base material, 25 parts of ethylene-vinyl acetate copolymer, 3.5 parts of hydrophobically modified montmorillonite, 25 parts of plasticizer, 1.5 parts of flame retardant, 1.2 parts of heat stabilizer, 0.8 parts of light stabilizer, 0.6 parts of ultraviolet absorber, and 0.6 parts of antioxidant.

[0028] The surface protection layer of the automotive film in Example 2 includes the following raw materials in parts by weight: 11 parts of silicone elastomer particles, 70 parts of base material, 25 parts of ethylene-vinyl acetate copolymer, 3.5 parts of hydrophobically modified montmorillonite, 25 parts of plasticizer, 1.5 parts of flame retardant, 1.2 parts of heat stabilizer, 0.8 parts of light stabilizer, 0.6 parts of ultraviolet absorber, and 0.6 parts of antioxidant.

[0029] The surface protection layer of the automotive film in Example 3 includes the following raw materials in parts by weight: 20 parts of silicone elastomer particles, 70 parts of base material, 25 parts of ethylene-vinyl acetate copolymer, 3.5 parts of hydrophobically modified montmorillonite, 25 parts of plasticizer, 1.5 parts of flame retardant, 1.2 parts of heat stabilizer, 0.8 parts of light stabilizer, 0.6 parts of ultraviolet absorber, and 0.6 parts of antioxidant.

[0030] The surface protection layer of the automotive film in Example 4 includes the following raw materials in parts by weight: 8 parts of silicone elastomer particles, 85 parts of base material, 8 parts of ethylene-vinyl acetate copolymer, 3 parts of hydrophobically modified montmorillonite, 20 parts of plasticizer, 2 parts of flame retardant, 2 parts of heat stabilizer, 2 parts of light stabilizer, 1 part of ultraviolet absorber, and 0.5 parts of antioxidant.

[0031] The surface protection layer of the automotive film in Example 5 includes the following raw materials in parts by weight: 15 parts of silicone elastomer particles, 60 parts of base material, 15 parts of ethylene-vinyl acetate copolymer, 5 parts of hydrophobically modified montmorillonite, 30 parts of plasticizer, 1 part of flame retardant, 1 part of heat stabilizer, 0.5 part of light stabilizer, 0.5 part of ultraviolet absorber, and 1 part of antioxidant.

[0032] The matrix material used in Examples 1-5 is a mixed material of TPU and TPO in a weight ratio of 2:1.

[0033] The silicone elastomer particles used in Examples 1-5 are grafted with acrylate groups and epoxy groups on their surfaces. The silicone elastomer particles grafted with epoxy and acrylate groups are model TP906D purchased from Yongqi Material Technology (Shanghai) Co., Ltd. and have a particle size range of 6-8 um.

[0034] The preparation process of the hydrophobically modified montmorillonite used in Examples 1-5 comprises the following steps: KH550 coupling agent was added to 75wt% ethanol solution to prepare a coupling agent solution with a mass fraction of KH550 coupling agent of 10wt%, and then montmorillonite was added, ultrasonically dispersed for 30 minutes, heated to 70-80°C, reacted for 1-2 hours, filtered to obtain the residue, and dried to obtain hydrophobically modified montmorillonite.

[0035] The particle size of the hydrophobically modified montmorillonite used in Examples 1-5 ranges from 2 to 5 μm.

[0036] The flame retardant used in Examples 1-5 is sodium hydroxymethyl lignin sulfonate and triphenyl phosphate in a weight ratio of 3:1. The preparation process of sodium hydroxymethyl lignin sulfonate includes the following steps: mixing sodium lignin sulfonate, formaldehyde and water in a weight ratio of 5:1:20, adjusting the pH to 12, distilling at 85°C for 5h, cooling to obtain a solution, and drying to obtain sodium hydroxymethyl lignin sulfonate (powder).

[0037] The content of vinyl acetate in the ethylene-vinyl acetate copolymer used in Examples 1-5 was 20 wt%.

[0038] The plasticizer used in Examples 1-5 was dioctyl terephthalate.

[0039] The heat stabilizer used in Examples 1-5 is a calcium-zinc powder composite stabilizer, which is an environmentally friendly calcium-zinc composite stabilizer of type MK-W5035 purchased from Maike High-Tech.

[0040] The light stabilizer used in Examples 1-5 was purchased from Light Stabilizer 783 from Liansheng Technology.

[0041] The antioxidant used in Examples 1-5 is a hindered phenol antioxidant, specifically antioxidant 2246.

[0042] The ultraviolet absorber used in Examples 1-5 is a benzotriazole ultraviolet absorber, specifically UV-326.

[0043] The method for preparing the automotive film in Examples 1-5 comprises the following steps: S1, drying the base material in a dryer to remove moisture, adding the dried base material and the remaining raw materials into a reaction vessel according to the formula amount for melt blending, controlling the temperature to 160° C., to obtain a premix; S2. Extruding the premix obtained in step S1 to form a uniform film, cooling it in cooling water, shaping it, and cutting it, coating a pressure-sensitive adhesive on one surface of the cut film to form a pressure-sensitive adhesive layer, and covering the pressure-sensitive adhesive layer with release paper to form a release layer, thereby obtaining a vehicle film containing silicone elastomer particles.

[0044] In step S2, the extrusion process is carried out in a twin-screw extruder, the speed of the twin-screw extruder is 100 rpm, the head temperature is 180-185°C, the temperature of zone 1 is 130-135°C, the temperature of zone 2 is 140-145°C, the temperature of zone 3 is 155-160°C, the temperature of zone 4 is 170-175°C, the temperature of zone 5 is 180-185°C, the temperature of zone 6 is 190-195°C, the temperature of zone 7 is 190-195°C, the temperature of zone 8 is 190-195°C, and the temperature of zone 9 is 180-185°C.

[0045] The thickness of the automotive film obtained in step S2 is controlled to be 1.2 mm, wherein the thickness of the surface protection layer is about 0.9 mm.

[0046] Embodiment 6-7 Example 6 is based on Example 2, with the difference that the base material in the surface protection layer of the automotive film in Example 6 is replaced by PVC.

[0047] Example 7 is based on Example 2, with the difference that the base material in the surface protection layer of the automotive film in Example 7 is replaced by TPU.

[0048] Embodiment 8-9 Example 8 is based on Example 2, with the difference that the silicone elastomer particles in the surface protection layer of the automotive film in Example 8 are replaced with silicone elastomer particles of model TP915D purchased from Yongqi Material Technology (Shanghai) Co., Ltd., with a particle size range of 12-15um.

[0049] Example 9 is based on Example 2, with the difference that the silicone elastomer particles in the surface protection layer of the automotive film in Example 9 are replaced with silicone elastomer particles of model TP902D purchased from Yongqi Material Technology (Shanghai) Co., Ltd., with a particle size range of 2-3um.

[0050] Example 10 Example 10 is based on Example 2, except that the flame retardant in the surface protective layer of the automotive film in Example 10 is replaced by an equal amount of triphenyl phosphate.

[0051] Embodiment 11 Example 11 is based on Example 2, except that in Example 11, an equal amount of the organic silicone elastomer particles in the surface protection layer of the automotive film are replaced by organic silicone elastomer particles without polar groups grafted onto the surface.

[0052] Comparative Example 1 Comparative Example 1 is based on Example 2, except that: in Comparative Example 1, an equal amount of the organic silicone elastomer particles in the surface protection layer of the automotive film are replaced by silicon dioxide with the same particle size.

[0053] Comparative Example 2 Comparative Example 2 is based on Example 2, except that: in Comparative Example 2, no hydrophobic modified montmorillonite is added to the surface protective layer of the automotive film.

[0054] Performance Testing 1. The 60° glossiness (%) of the automotive films prepared in Examples 1-11 and Comparative Examples 1-2 was measured with reference to the standard GB / T9754-2007.

[0055] 2. The wear resistance (mg) of the automotive films prepared in Examples 1-11 and Comparative Examples 1-2 was measured by the Taber wear test specified in the standard ASTM D 4060 test method. At this time, the wear wheel used was H18, the load was 1 kg, the initial wear was 100 times, and the rotation speed was 60 rpm. The smaller the measured mass loss value (mg), the better the wear resistance.

[0056] 3. The index finger was slid on the surface protective layer of the automotive film prepared in Examples 1-11 and Comparative Examples 1-2 to evaluate the touch.

[0057] 4. The flame retardant properties of the automotive films prepared in Examples 1-11 and Comparative Examples 1-2 were measured with reference to the UL-94-2006 standard.

[0058] The measurement results are shown in Table 1.

[0059] surface By analyzing the data in Table 1, it can be found that in Examples 1-11, the surface of the automotive film prepared in Example 9 has a slightly matte effect, and the surface gloss is about 20%; while the surfaces of other examples have a significant matte effect, and the surface gloss is less than 10% or about 10%. In summary, the automotive film prepared in this application has both good wear resistance and a more comfortable touch. At the same time, the surface gloss effect of the automotive film can be adjusted by controlling the particle size and dosage of the silicone elastomer particles.

[0060] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A film for automobile containing silicone elastomer particles, It is characterized in that It comprises a surface protection layer, the lower surface of which is provided with a pressure-sensitive adhesive layer and a release layer in sequence; The surface protection layer comprises the following raw materials in parts by weight: 60-85 parts of base material, 5-20 parts of silicone elastomer particles, 20-30 parts of plasticizer, 1-2 parts of heat stabilizer, 0.5-2 parts of light stabilizer, 0.5-1 parts of antioxidant, 0.5-1 parts of ultraviolet absorber, 1-2 parts of flame retardant, 3-5 parts of hydrophobically modified montmorillonite, and 8-15 parts of ethylene-vinyl acetate copolymer.

2. The film for automobile containing silicone elastomer particles according to claim 1, It is characterized in that The matrix material includes one or more of TPO, TPU and PVC.

3. The film for automobile containing silicone elastomer particles according to claim 1, It is characterized in that Polar groups are grafted onto the surface of the organic silicon elastomer particles, and the polar groups include two or more of acrylate groups, acrylonitrile groups, epoxy groups and amino groups.

4. The film for automobile containing silicone elastomer particles according to claim 1, It is characterized in that The particle size of the organic silicon elastomer particles is 2-3 um.

5. The film for automobile containing silicone elastomer particles according to claim 1, It is characterized in that The particle size of the organic silicone elastomer particles is 6-8 um, or the particle size of the organic silicone elastomer particles is 12-15 um.

6. The film for automobile containing silicone elastomer particles according to claim 1, It is characterized in that The hydrophobically modified montmorillonite is cross-linked and modified by using KH550 coupling agent.

7. The film for automobile containing silicone elastomer particles according to claim 1, It is characterized in that The flame retardant comprises a weight ratio of 1-3: A mixture of 0.5-1 sodium hydroxymethyl lignin sulfonate and triphenyl phosphate.

8. A method for preparing a vehicle film containing silicone elastomer particles according to any one of claims 1 to 7, It is characterized in that The following steps are involved: S1, drying the base material in a dryer to remove moisture, adding the dried base material and the remaining raw materials into a reaction vessel according to the formula amount for melt blending, controlling the temperature to 150-180° C., to obtain a premix; S2. Extruding the premix obtained in step S1 to form a uniform film, cooling it in cooling water, shaping it, and cutting it, coating a pressure-sensitive adhesive on one surface of the cut film to form a pressure-sensitive adhesive layer, and covering the pressure-sensitive adhesive layer with release paper to form a release layer, thereby obtaining a vehicle film containing silicone elastomer particles.

9. The method for preparing a film for automobile containing silicone elastomer particles according to claim 8, It is characterized in that In the step S2, the extrusion process is carried out in a twin-screw extruder, the temperature of zone 1 of the twin-screw extruder is 130-135°C, the temperature of zone 2 is 140-145°C, the temperature of zone 3 is 155-160°C, the temperature of zone 4 is 170-175°C, the temperature of zone 5 is 180-185°C, the temperature of zone 6 is 190-195°C, the temperature of zone 7 is 190-195°C, the temperature of zone 8 is 190-195°C, and the temperature of zone 9 is 180-185°C; the rotation speed of the twin-screw extruder is 100-120rpm; and the head temperature of the twin-screw extruder is 180-185°C.